If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5c + 2 = 23 Reorder the terms: 2 + -5c = 23 Solving 2 + -5c = 23 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -5c = 23 + -2 Combine like terms: 2 + -2 = 0 0 + -5c = 23 + -2 -5c = 23 + -2 Combine like terms: 23 + -2 = 21 -5c = 21 Divide each side by '-5'. c = -4.2 Simplifying c = -4.2
| -16+11x=14+10x | | 28y-14=21y+10.5 | | -5c+2=-21 | | 3x^2+x^2-3x-1=0 | | -65-x=-6x+20 | | x-16=-22x | | 17(6c-1)-10=100c+17 | | 4x^3-456x=0 | | -81+12x=171-9x | | 3x+7=11+2x | | h(x)=-x^4+5x^2-4 | | 2x+0.5x-10=10 | | w^2+10w-2475=0 | | 8/5(t-6)=0.4 | | -x-58=-6x+47 | | .5x+3.5=4x-7 | | 2x^2-12x-56=0 | | 5x-63=-3x+33 | | 54/100 | | 4/12=18/x | | 1/4q=20 | | -19-7x=39-9x | | 2.20x=12 | | -5(t-1)+7t=5t-3 | | log(10-4x)=log(10x-3x) | | 1/2*2/67 | | 4P=T-5R+6forR | | 7x-35=28+4x | | 4x(2x-1)=7 | | 5x+2-7(x+1)=7x+2 | | 3+6x=27+6 | | -63-x=-7x+27 |